Progress and Priorities in Ocean Drilling: In Search of Earth's Past and Future - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Research supported by scientific ocean drilling has fundamentally transformed our understanding of the planet with key contributions to the discovery and theory of plate tectonics; the formation and destruction of ocean crust; the reconstruction of extreme greenhouse and icehouse climates; the identification of major extinctions; and the discovery of a diverse community of microbes living deep ocean seafloor. With the retirement in 2024 of the JOIDES Resolution-- the U.S. dedicated drilling vessel for deep sea research and the workhorse for the international scientific ocean drilling community-- the scientific ocean drilling landscape will change. At this critical juncture, the National Science Foundation (NSF) is looking to identify the most urgent research questions that can only be answered with scientific ocean drilling and what infrastructure is needed to progress those priorities. This interim report that is the first part of a broader study of decadal survey of ocean science provides a broad perspective of future research and associated infrastructure needs. The report concludes that the rapid pace of climate change, related extreme events, sea level rise, changes in ocean currents, chemistry threatening ocean ecosystems, and devastating natural hazards are among the greatest challenges facing society. By coring the past to inform the future, U.S. based scientific ocean drilling research continues to have unique and essential roles in addressing these vital and urgent challenges.
Keywords: Earth Sciences

Supporting Family Caregivers in STEMM: A Call to Action - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Family caregiving is not simply an outside obligation that has no bearing on the workings of academic science, technology, engineering, mathematics, and medicine (STEMM) as it affects the lives of so many people working and studying in colleges and universities around the country. Caregiving responsibilities often clash with ingrained norms in academic STEMM environments, which demand that STEMM students and workers demonstrate immense devotion to their fields and are always available and visibly working. Supporting Family Caregivers in STEMM describes the ways in which the labor and contributions of caregivers are often invisible and undervalued, with a specific focus on the academic STEMM ecosystem, including undergraduate and graduate students, postdoctoral scholars, resident physicians and other trainees, tenure-track and non-tenure-track faculty, staff, and researchers. This report reviews policies and practices that support caregivers, locally and nationally, and describes best practices in policy implementation and design. Supporting Family Caregivers in STEMM also highlights innovative practices and offers actionable recommendations to higher education institutions, public and private funders, and the federal government.
Keywords: Industry and Labor

A Roadmap for Disclosure Avoidance in the Survey of Income and Program Participation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The Survey of Income and Program Participation (SIPP) is one of the U.S. Census Bureau’s major surveys with features making it a uniquely valuable resource for researchers and policy analysts. However, the Census Bureau faces the challenge of protecting the confidentiality of survey respondents which has become increasingly difficult because numerous databases exist with personal identifying information that collectively contain data on household finances, home values, purchasing behavior, and other SIPP-relevant characteristics. A Roadmap for Disclosure Avoidance in the Survey of Income and Program Participation addresses these issues and how to make data from SIPP available to researchers and policymakers while protecting the confidentiality of survey respondents. The report considers factors such as evolving privacy risks, development of new methods for protecting privacy, the nature of the data collected through SIPP, the practice of linking SIPP data with administrative data, the types of data products produced, and the desire to provide timely access to SIPP data. The report seeks to balance minimizing the risk of disclosure against allowing researchers and policymakers to have timely access to data that support valid inferences.
Keywords: Behavioral and Social Sciences

Social Media and Adolescent Health - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Social media has been fully integrated into the lives of most adolescents in the U.S., raising concerns among parents, physicians, public health officials, and others about its effect on mental and physical health. Over the past year, an ad hoc committee of the National Academies of Sciences, Engineering, and Medicine examined the research and produced this detailed report exploring that effect and laying out recommendations for policymakers, regulators, industry, and others in an effort to maximize the good and minimize the bad. Focus areas include platform design, transparency and accountability, digital media literacy among young people and adults, online harassment, and supporting researchers.
Keywords: Health and Medicine

The Role of Seafood Consumption in Child Growth and Development - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Seafood--including marine and freshwater fish, mollusks, and crustaceans--is a healthy food choice, but it can also contain contaminants. It is currently unclear how much seafood children or pregnant and lactating women are consuming, and what impact seafood consumption is having on children's growth and development.The U.S. Department of Health and Human Services, the U.S. Department of Agriculture, the U.S. Environmental Protection Agency, and the National Oceanic and Atmospheric Administration tasked the National Academies of Sciences, Engineering, and Medicine with convening an expert committee to examine associations between seafood intake for children, adolescents, and pregnant and lactating women and child growth and development. The committee also evaluated when to conduct risk-benefit analyses (RBAs), while considering contextual factors such as equity, diversity, inclusion, and access to health care, and explored how these factors might impact RBAs.
Keywords: Health and Medicine; Food and Nutrition

Foundational Research Gaps and Future Directions for Digital Twins - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Across multiple domains of science, engineering, and medicine, excitement is growing about the potential of digital twins to transform scientific research, industrial practices, and many aspects of daily life. A digital twin couples computational models with a physical counterpart to create a system that is dynamically updated through bidirectional data flows as conditions change. Going beyond traditional simulation and modeling, digital twins could enable improved medical decision-making at the individual patient level, predictions of future weather and climate conditions over longer timescales, and safer, more efficient engineering processes. However, many challenges remain before these applications can be realized. This report identifies the foundational research and resources needed to support the development of digital twin technologies. The report presents critical future research priorities and an interdisciplinary research agenda for the field, including how federal agencies and researchers across domains can best collaborate.
Keywords: Computers and Information Technology; Math, Chemistry, and Physics

Forum on Regenerative Medicine: 2023 Annual Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The Forum on Regenerative Medicine aspires to spark exchange and inspire action among diverse interested parties to advance regenerative medicine for the benefit of all. During 2023, the forum members focused on three broad areas through their working groups: Diversity, Equity, and Inclusion; Manufacturing and Supply Chain; and Workforce Development. The members and staff also explored challenges and discussed possible solutions in a number of other areas relevant to the development of regenerative medicines, including communication, cost of and access to therapies, and regulatory and legislative affairs. This publication describes the activities of the forum during 2023.
Keywords: Health and Medicine

Forum on Drug Discovery, Development, and Translation: 2023 Annual Review - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
In 2023, the Forum on Drug Discovery, Development, and Translation focused on diverse topics, including approaches to define and evaluate in-home drug disposal systems for opioid analgesics, the diagnosis and treatment of adults with attention-deficit/hyperactivity disorder and implications for drug development, strategies to optimize public–private partnerships for clinical cancer research, opportunities to prepare the future workforce in research and development, and other policy updates relevant to drug discovery, development, and translation. Learn more in this 2023 Annual Review.
Keywords: Health and Medicine

Roundtable on Population Health Improvement: Annual Report 2023 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The Roundtable on Population Health Improvement was established in February 2013 to bring together philanthropy, community-based organizations, health care delivery, governmental public health, academia, and business in a wide-ranging dialogue about what is needed to improve health in the United States and across diverse populations. In 2023, the roundtable hosted workshops, webinars, and other activities that continued its exploration of the social drivers of health of past and persisting racially unjust systems and structures that shape those drivers.
Keywords: Health and Medicine

Roundtable on Genomics and Precision Health: 2023 Annual Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
The members and staff of the Roundtable on Genomics and Precision Health continue to work toward their vision of realizing the full potential of health for all through genomics and precision health by bringing together diverse voices to encourage innovation and actions that foster the wide adoption of and equitable access to the benefits of genomics and precision health. During 2023, roundtable members explored topics such as equity in the return of results for large datasets; clinical guideline development for genomic testing; the promise and perils of DNA sequencing of newborns at birth; perspectives on the proposed laboratory-developed test regulation; engaging communities and building trust in genomics; and biomarker legislation related to genetic testing.
Keywords: Health and Medicine

Charting a Future for Sequencing RNA and Its Modifications: A New Era for Biology and Medicine - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Concerted efforts to deepen understanding of RNA modifications and their role in living systems hold the potential to advance human health, improve crop yields, and address other pressing societal challenges. RNA, which carries the information encoded by DNA to the places where it is needed, is amazingly diverse and dynamic. RNA is processed and modified through natural biological pathways, giving rise to hundreds, in some cases thousands, of distinct RNA molecules for each gene, thereby diversifying genetic information. RNA modifications are known to be pivotal players in nearly all biological processes, and their dysregulation has been implicated in a wide range of human diseases and disorders. Yet, our knowledge of RNA modifications remains incomplete, hindered by current technological limitations. Existing methods cannot discover all RNA modifications, let alone comprehensively sequence them on every RNA molecule. Nonetheless, what is known about RNA modifications has already been leveraged in the development of vaccines that helped saved millions of lives worldwide during the COVID-19 pandemic. RNA modifications also have applications beyond health, for example, enhancing agricultural productivity. Charting a Future for Sequencing RNA and Its Modifications: A New Era for Biology and Medicine calls for a focused, large-scale effort to accelerate technological innovation to harness the full potential of RNA modifications to address pressing societal challenges in health, agriculture, and beyond. This report assesses the scientific and technological breakthroughs, workforce, and infrastructure needs to sequence RNA and its modifications, and ultimately understand the roles RNA modifications play in biological processes and disease. It proposes a roadmap of innovation that will make it possible for any RNA from any biological system to be sequenced end-to-end with all of its modifications - a capability that could lead to more personalized and targeted treatments and instigate transformative changes across various sectors beyond health and medicine.
Keywords: Biology and Life Sciences; Health and Medicine

Evidence Review of the Adverse Effects of COVID-19 Vaccination and Intramuscular Vaccine Administration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Vaccines are a public health success story, as they have prevented or lessened the effects of many infectious diseases. To address concerns around potential vaccine injuries, the Health Resources and Services Administration (HRSA) administers the Vaccine Injury Compensation Program (VICP) and the Countermeasures Injury Compensation Program (CICP), which provide compensation to those who assert that they were injured by routine vaccines or medical countermeasures, respectively. The National Academies of Sciences, Engineering, and Medicine have contributed to the scientific basis for VICP compensation decisions for decades. HRSA asked the National Academies to convene an expert committee to review the epidemiological, clinical, and biological evidence about the relationship between COVID-19 vaccines and specific adverse events, as well as intramuscular administration of vaccines and shoulder injuries. This report outlines the committee findings and conclusions.
Keywords: Health and Medicine

Enhancing EPA Science Capability for a Complex Future: Recommendations for Use of Title 42 Special Hiring Authority - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
A scientific workforce with cutting-edge skills is critical for the ability of the U.S. Environmental Protection Agency to carry out its mission to protect human health by identifying environmental hazards, evaluating risks to public health and ecosystems, and formulating effective methods for pollution control and prevention. To aid in the selection and hiring of premier scientists and engineers, in 2006, EPA first sought the ability to directly recruit world-renowned scientists and engineers from academia, private industry, and other government agencies under Title 42, Section 209, of the U.S. Code. Title 42 authorizes federal agencies to appoint highly qualified scientists and engineers outside of standard civil service positions. Congress reauthorizes the EPA Title 42 authority in 5-year increments. To guide decisions about the future of the program, Congress asked the National Academies to review past and current EPA use of Title 42 hiring authority and how the program might be improved. The report finds that EPA has used its limited Title 42 authority effectively since 2006 and that Title 42 authority has enabled the hiring of effective scientific leadership and improved the scientific capability and capacity to support the Agency mission. Furthermore, the report finds that Title 42 can help the agency in addressing future environmental complexities. In continuing to enhance its scientific workforce and maintain a position at the forefront of evolving scientific knowledge, EPA would benefit from Congressional approval for permanent Title 42 authority.
Keywords: Environment and Environmental Studies

An Assessment of the National Institute of Standards and Technology Center for Neutron Research: Fiscal Year 2023 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Since 1959, the National Institute of Standards and Technology (NIST) has annually enlisted the National Academies of Sciences, Engineering, and Medicine to convene expert panels comprising individuals from academia, industry, and various scientific and engineering fields. Their primary task is to evaluate the quality and efficacy of the six NIST measurements and standards laboratories, as well as the sufficiency of resources available to these laboratories. This report assesses the NIST Center for Neutron Research (NCNR), with a focus on scientific and technical programs; portfolio of scientific and technical expertise; the adequacy of the budget, facilities, instrumentation, and human resources; and the effectiveness of NCNR dissemination efforts.
Keywords: Engineering and Technology

Toward a 21st Century National Data Infrastructure: Managing Privacy and Confidentiality Risks with Blended Data - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Protecting privacy and ensuring confidentiality in data is a critical component of modernizing our national data infrastructure. The use of blended data - combining previously collected data sources - presents new considerations for responsible data stewardship. Toward a 21st Century National Data Infrastructure: Managing Privacy and Confidentiality Risks with Blended Data provides a framework for managing disclosure risks that accounts for the unique attributes of blended data and poses a series of questions to guide considered decision-making. Technical approaches to manage disclosure risk have advanced. Recent federal legislation, regulation and guidance has described broadly the roles and responsibilities for stewardship of blended data. The report, drawing from the panel review of both technical and policy approaches, addresses these emerging opportunities and the new challenges and responsibilities they present. The report underscores that trade-offs in disclosure risks, disclosure harms, and data usefulness are unavoidable and are central considerations when planning data-release strategies, particularly for blended data.
Keywords: Behavioral and Social Sciences

Advancing Clinical Research with Pregnant and Lactating Populations: Overcoming Real and Perceived Liability Risks - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Congress called on the National Academies to convene a committee to examine the real and perceived risks of liability arising from research conducted with pregnant and lactating women. The resulting report, Clinical Research with Pregnant and Lactating Populations: Overcoming Real and Perceived Liability Risks, explores and finds limited evidence of legal liability for inclusion of pregnant and lactating women in clinical research, contradicting perceptions of heightened liability. The committee also makes recommendations that could lead to a more robust evidence base about the safety and efficacy of medications for pregnant and lactating women that would facilitate more informed decision making regarding care while mitigating liability.
Keywords: Health and Medicine

Reducing Intergenerational Poverty - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Experiencing poverty during childhood can lead to lasting harmful effects that compromise not only children’s health and welfare but can also hinder future opportunities for economic mobility, which may be passed on to future generations. This cycle of economic disadvantage weighs heavily not only on children and families experiencing poverty but also the nation, reducing overall economic output and placing increased burden on the educational, criminal justice, and health care systems. Reducing Intergenerational Poverty examines key drivers of long- term, intergenerational poverty, including the racial disparities and structural factors that contribute to this cycle. The report assesses existing research on the effects on intergenerational poverty of income assistance, education, health, and other intervention programs and identifies evidence-based programs and policies that have the potential to significantly reduce the effects of the key drivers of intergenerational poverty. The report also examines the disproportionate effect of disadvantage to different racial/ethnic groups. In addition, the report identifies high-priority gaps in the data and research needed to help develop effective policies for reducing intergenerational poverty in the United States.
Keywords: Behavioral and Social Sciences

Facial Recognition Technology: Current Capabilities, Future Prospects, and Governance - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Facial recognition technology is increasingly used for identity verification and identification, from aiding law enforcement investigations to identifying potential security threats at large venues. However, advances in this technology have outpaced laws and regulations, raising significant concerns related to equity, privacy, and civil liberties. This report explores the current capabilities, future possibilities, and necessary governance for facial recognition technology. Facial Recognition Technology discusses legal, societal, and ethical implications of the technology, and recommends ways that federal agencies and others developing and deploying the technology can mitigate potential harms and enact more comprehensive safeguards.
Keywords: Computers and Information Technology; Behavioral and Social Sciences; Engineering and Technology

Health Risks of Indoor Exposure to Fine Particulate Matter and Practical Mitigation Solutions - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Schools, workplaces, businesses, and even homes are places where someone could be subjected to particulate matter (PM) – a mixture of solid particles and liquid droplets found in the air. PM is a ubiquitous pollutant comprising a complex and ever-changing combination of chemicals, dust, and biologic materials such as allergens. Of special concern is fine particulate matter (PM2.5), PM with a diameter of 2.5 microns (<0.0001 inch) or smaller. Fine PM is small enough to penetrate deep into the respiratory system, and the smallest fraction of it, ultrafine particles (UFPs), or particles with diameters less than 0.1 micron, can exert neurotoxic effects on the brain. Overwhelming evidence exists that exposure to PM2.5 of outdoor origin is associated with a range of adverse health effects, including cardiovascular, pulmonary, neurological and psychiatric, and endocrine disorders as well as poor birth outcomes, with the burden of these effects falling more heavily on underserved and marginalized communities. Health Risks of Indoor Exposure to Fine Particulate Matter and Practical Mitigation Solutions explores the state-of the-science on the health risks of exposure to fine particulate matter indoors along with engineering solutions and interventions to reduce risks of exposure to it, including practical mitigation strategies. This report offers recommendations to reduce population exposure to PM2.5, to reduce health impacts on susceptible populations including the elderly, young children, and those with pre-existing conditions, and to address important knowledge gaps.
Keywords: Health and Medicine; Engineering and Technology

Accelerating Decarbonization in the United States: Technology, Policy, and Societal Dimensions - Transportation Research Board; National Academy of Engineering; National Academy of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Addressing climate change is essential and possible, and it offers a host of benefits - from better public health to new economic opportunities. The United States has a historic opportunity to lead the way in decarbonization by transforming its current energy system to one with net-zero emissions of carbon dioxide. Recent legislation has set the nation on the path to reach its goal of net zero by 2050 in order to avoid the worst consequences of climate change. However, even if implemented as designed, current policy will get the United States only part of the way to its net-zero goal. Accelerating Decarbonization in the United States provides a comprehensive set of actionable recommendations to help policymakers achieve a just and equitable energy transition over the next decade and beyond, including policy, technology, and societal dimensions. This report addresses federal and subnational policy needs to overcome implementation barriers and gaps with a focus on energy justice, workforce development, public health, and public engagement. The report also presents a suite of recommendations for the electricity, transportation, built environment, industrial, fossil fuels, land use, and finance sectors.
Keywords: Environment and Environmental Studies; Earth Sciences